Men Working with Men in Intensive Family Services: Reflections on Violence, Trauma Lifeworlds, and Organic Interventions. Issue 4 (20th November 2022) - Haines, Alex; Andary, Stuart; Amos, Jackie; Louth, Jonathon; Mannik, Amalie; Jacobs, Ruth; Best, Paul; Calio, Paul; Petrovic, Travis; Scott, Ryan; Vlahos, Alex
Abstract : Intimate partner violence is a major problem in Australia, impacting many families that are on the cusp of disruption and intervention by the child protection system. Using an innovative method of inquiry, the article explores the role of dedicated men's workers in a South Australian non‐government organisation's intensive family service that works towards keeping families safe and together. The dedicated men's worker positions are integrated into a multidisciplinary model that works with fathers who have been a part of situational violence within the family. The men's workers' (and co‐authors') reflections offer insight into systemic barriers, practical therapeutic interventions, engagement work with fathers, how this is approached, and the various outcomes experienced. Blending auto‐ethnography reflections, elements of rapid ethnographic assessment, and the use of rigorous and accelerated data reduction, we demonstrate the need for increased supports for some fathers. These should include therapeutic engagement and working with the underlying trauma of fathers to ensure the whole family is supported and offered opportunity for healing and sustainable preservation. We also consider the more encompassing lifeworlds of the men and the need to drive and support broader sociocultural shifts.